Generalized Moment Representations and Padé Approximants Associated with Bilinear Transformations - Golub, A.P. (Український математичний журнал, 2002)
By using the method of generalized moment representations with an operator of bilinear transformation of an independent variable, we construct elements of the first subdiagonal of the Padé table for certain special power series.